PENERAPAN MODEL DISCOVERY LEARNING DALAM MENINGKATKAN APRESIASI CERPEN “SAY NO TO CORRUPTION” PADA SISWA KELAS VIII SMP PGRI OTAM - Astriya Pobela; Donal M. Ratu; Oldie Stevie Meruntu (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to describe the implementation of the Discovery Learning model and students’ ability to appreciate the short story “The Courage of a Young Man: Say No to Corruption” by Rica Elisa among Grade VIII students of SMP PGRI Otam, Bolaang Mongondow Regency. The study used a descriptive-analytic method with data collection techniques in the form of observation and tests.The implementation of the Discovery Learning model was carried out through several stages, namely lesson planning by preparing teaching materials and the short story text, preliminary activities including opening the lesson, conveying objectives, and explaining the learning model, as well as core activities involving the distribution of worksheets. At this stage, students appreciated the short story by observing characters and characterization, identifying the plot, collecting data related to conflicts, drawing conclusions about the content of the story, and presenting the results of discussions.The results of the study show that students’ ability to appreciate short stories is categorized as capable. Three students were in the “very capable” category with a score range of 90–100, ten students were in the “capable” category with a score range of 80–90, two students were in the “fairly capable” category with a score range of 70–79, and one student was in the “not capable” category with a score range of 0–69. The average score achieved by students reached 80%. Therefore, the implementation of the Discovery Learning model is effective in improving students’ ability to appreciate short stories. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan model Discovery Learning serta kemampuan siswa dalam mengparesiasi cerpen “Keberanian Seorang Pemuda Say No To Corruption” Karya Rica Elisa pada siswa kelas VIII SMP PGRI Otam Kabupaten Bolaang Mongondow. Penelitian ini menggunakan metode deskriptif analtik dengan Teknik pengumpulan data berupa observasi dan tes. Penerapan model Discovery Learning dilakukan melalui beberapa tahapan, yaitu perencanaan pembelajaran dengan menyiapkan modul ajar dan teks cerpen, kegiatan pendahuluan berupa pembukaan, penyampaian tujuan, dan penjelasan model pembelajaran, serta kegiatan inti dengan pemberian lembar kerja. Pada tahap ini, siswa mengapresiasi cerpen dengan mengamati tokoh dan penokohan, mengidentifikasi alur, mengumpulkan data terkait konflik, menarik Kesimpulan isi cerpen, serta mempresentasikan hasil diskusi. Hasil penelitian menunjukan bahwa kemampuan siswa dalam mengapresiasi cerpen tergolong mampu, tiga siswa berada pada kategori sangat mampu dengan rentang nilai 90-100, sepuluh siswa pada kategori mampu dengan rentang nilai 80-90, dua siswa pada kategori mampu dengan rentang nilai 70-79, dan satu siswa pada kategori tidak mampu dengan rentang nilai 0-69. Nilai rata-rata yang diperoleh siswa menncapai 80%. Dengan demikian, penerapan model Discovery Learning efektif dalam meningkatkan kemampuan siswa dalam mengapresiasi cerpen.